2021
DOI: 10.1177/01655515211040658
|View full text |Cite
|
Sign up to set email alerts
|

‘Access necessitates being seen’: Queer visibility and intersectional embodiment within the health information practices of queer community leaders

Abstract: Navigating healthcare infrastructures is particularly challenging for queer-identifying individuals, with significant barriers emerging around stigma and practitioner ignorance. Further intersecting, historically marginalised identities such as one’s race, age or ability exacerbate such engagement with healthcare, particularly the access to and use of reliable and appropriate health information. We explore the salience of one’s queer identity relative to other embodied identities when navigating health informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Thus far, we have been generalizing lived experiences among LGBTQIA+ communities. Though such generalizations convey important commonalities among community members' information practices, they also threaten to represent marginalized communities as monoliths Wagner and Kitzie (2021). Understanding embodied information practices become essential to avoid this reductive mistake.…”
Section: Locating Community and Self Within Defensive And Protective ...mentioning
confidence: 99%
“…Thus far, we have been generalizing lived experiences among LGBTQIA+ communities. Though such generalizations convey important commonalities among community members' information practices, they also threaten to represent marginalized communities as monoliths Wagner and Kitzie (2021). Understanding embodied information practices become essential to avoid this reductive mistake.…”
Section: Locating Community and Self Within Defensive And Protective ...mentioning
confidence: 99%
“…In recognizing that one's information behavior can be related to one's association with a marginalized group, Chatman draws attention to the nature of the inequality between the information behavior of a marginalized social group, which was explored in this study. Chatman's theory of information poverty has also been explored in many situations with examples including but not limited to the information world of female prisoners (Chatman, 1999), the information world of the homeless (Hersberger, 2002/2003), young men who have sex with other men (Veinot et al, 2013), and health information practices of the queer community (Wagner & Kitzie, 2021). Haider and Bawden (2007) used discourse analysis to gain an understanding of how the concept of information poverty is described in LIS research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The perception of context collapse will motivate people to engage in privacy management activities to reevaluate and recalibrate the privacy rules. Many previous studies have found that LGBTQþ individuals would conduct protective and defensive information practices (Kitzie et al, 2022), and employ various tactics for being strategically visible and avoiding context collapse, such as creating multiple profiles, tailoring disclosed contents, separating audiences (Carrasco and Kerne, 2018;Duguay, 2016;Hanckel et al, 2019;Triggs et al, 2021;Wagner and Kitzie, 2021). Hence, we propose that:…”
Section: Boundary Turbulence and Coordinationmentioning
confidence: 99%